The new invasive mosquito species Aedes koreicus as vector-borne diseases in the European area, a focus on Italian region: What we know from the scientific literature - Ganassi, Sonia; De Cristofaro, Antonio; Di Criscio, Dalila; Petrarca, Sonia; Leopardi, Chiara; Guarnieri, Antonio; Pietrangelo, Laura; Venditti, Noemi; Di Marco, Roberto; Petronio Petronio, Giulio (Frontiers in Microbiology, 2022)
The increased mobility of goods, people, and animals worldwide has caused the spread of several arthropod vectors, leading to an increased risk of animal and human infections. Aedes koreicus is a common species in South Korea, China, Japan, and Russia. Due to its cold-resistant dormant eggs, the adults last from the late summer until the autumn seasons. For these reasons, it seems to be better adapted to colder temperatures, favouring its colonisation of hilly and pre-alpine areas. Its first appearance in Europe was in 2008 in Belgium, where it is currently established. The species was subsequently detected in Italy in 2011, European Russia, Germany, the Swiss-Italian border region, Hungary, Slovenia, Crimea, Austria, the Republic of Kazakhstan and the Netherlands. The role of Ae. koreicus in the transmission of vector-borne pathogens remains unclear. The available scientific evidence is very old, often not available in English or not indexed in international databases, and therefore difficult to find. According to the literature reviewed, Ae. koreicus can be considered a new invasive mosquito species in Europe, establishing populations on the European continent. In addition, experimental evidence demonstrated its vector competence for both D. immitis, Chikungunya and is relatively low for ZIKA but not for Western Nile Virus. On the other hand, even if the field evidence does not confirm the experimental findings, it is currently not possible to exclude with absolute certainty the potential involvement of this species in the spread, emergence, or re-emergence of these vector-borne disease agents.